Remote not distant design a company culture that will help you thrive in a hybrid workplace - Razzetti, Gustavo 1967- (Tantor Media, Inc., 2023)
Hybrid and remote work is here to stay. What will it take for your company to succeed in the new normal? The pandemic taught many businesses a very valuable lesson-those who don't adapt will get left behind. Some businesses managed to not only survive but actually thrive in a remote and hybrid work model. What's their secret? Top culture thought leader Gustavo Razzetti answers this question in this practical, meticulously researched book. The author and consultant provides a roadmap to understand, adapt to, and succeed in a hybrid workplace. After spending years studying businesses, including Amazon, Slack, GitLab, Volvo, Microsoft, and other successful organizations, his solid grasp of the topic will challenge your perspective of hybrid and remote work. Remote, Not Distant provides actionable tools for senior leaders, managers, team members, and consultants. Razzetti addresses the multiple areas of culture, from keeping your team connected and improving remote collaboration to managing asynchronous communication, facilitating courageous conversations, and defining the right hybrid model for your organization.
Online resource; title from title details screen (O'Reilly, viewed September 26, 2023)
Keywords: Flexible work arrangements -- United States; Telecommuting -- United States; Home labor -- United States; Labor productivity; Virtual work teams -- Management; Corporate culture; Organizational behavior; Organizational effectiveness; Organizational change; Career development; Flexible work arrangements; Home labor; Telecommuting; Virtual work teams; Management; United States; Audiobooks